(untitled) (Pragyaratna प्रज्ञारत्न, 2025)
Mortality is one of the most important indicators of demographic changes. It refers to the number of deaths per thousand mid-year population in a given period of time. The study was based on library based and descriptive research. It was based on secondary data that were selected purposively. The primary purpose of this study was to examine trends and differential factors in infant, child, and maternal mortality in Nepal. This study was based on secondary data from the Central Bureau of Statistics (CBS), the Nepal Demographic and Health Surveys (NDHS), and other relevant research reports, that applied descriptive methods. The researcher found that mortality has gradually declined in Nepal, due to the better health care services, educational improvements, and awareness regarding regular health checkups, delayed marriage, appropriate age for first child and improvement in the services of antenatal and postnatal care. In the case of infant mortality rate (IMR), the differences in number from 172 deaths per thousand live births in 1961 to 28 in 2022. Likewise, child mortality and under-five mortality also declined significantly across both sexes, though determined gender disparities continue. Additionally, maternal mortality rate (MMR), was 515 deaths per lakh live births in 1991, and decreased sharply to 151 in 2021. However, this positive progress regarding mortality, there is the geographical barriers, social- economic and cultural inequalities, and limited access to quality of health facilities particularly in rural areas. This study further explored that the outcomes of mortality area determined by health awareness, income and facilities.